2000
DOI: 10.1038/sj.cdd.4400687
|View full text |Cite
|
Sign up to set email alerts
|

Inducible expression of filaggrin increases keratinocyte susceptibility to apoptotic cell death

Abstract: Filaggrin is an intermediate filament associated protein that aids the packing of keratin filaments during terminal differentiation of keratinocytes. Premature aggregation of keratin filaments is prevented by filaggrin expression as the inactive precursor, profilaggrin, which is localized in keratohyalin granules in vivo. We have previously shown that filaggrin constructs, when transiently transfected into epithelial cells, lead to a collapsed keratin cytoskeletal network and dysmorphic nuclei with features of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 38 publications
3
27
0
Order By: Relevance
“…Filaggrin has been shown to be associated with nuclear degradation and keratin intermediate filament aggregation. 28,29 Studies have reported that keratohyalin granules with profilaggrin aggregates localise to the perinuclear region sometimes forming deep invaginations at the areas of association. 28,29 This is thought to facilitate entry of cleaved N-terminal domain of profilaggrin into the nucleus, where it favours nuclear degradation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Filaggrin has been shown to be associated with nuclear degradation and keratin intermediate filament aggregation. 28,29 Studies have reported that keratohyalin granules with profilaggrin aggregates localise to the perinuclear region sometimes forming deep invaginations at the areas of association. 28,29 This is thought to facilitate entry of cleaved N-terminal domain of profilaggrin into the nucleus, where it favours nuclear degradation.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Studies have reported that keratohyalin granules with profilaggrin aggregates localise to the perinuclear region sometimes forming deep invaginations at the areas of association. 28,29 This is thought to facilitate entry of cleaved N-terminal domain of profilaggrin into the nucleus, where it favours nuclear degradation. 28 One potential explanation for the altered processing of filaggrin, partially supported by our data, is that filaggrin interacts with nuclear lamins and therefore the persistence of Lamin A/C increases its association with filaggrin intermediates at the nuclear lamina, preventing its processing to more mature forms.…”
Section: Discussionmentioning
confidence: 99%
“…These cytokines are also expressed through similar pathways under magnesium deficient conditions (Miyazawa M et al 2008;Lee et al 2011). This TNF-a increase acts as an apoptotic signal, in response to which the keratinocytes are primed by FLG to aid its terminal differentiation, leading to the formation of corneocytes (Raj et al 2006;Kuechle et al 2000). We found that when excised skin was pre-treated with magnesium or calcium salts and subsequently stimulated with DNCB and TS, the FLG levels are always lower than that of the unstimulated salt treated skin (except in the case of 1.9M MgCl 2 stimulated with DNCB, section 6.3.3).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned earlier, the epidermal cells undergo continuous differentiation leading to terminal differentiation where stratum granulosum cells are anucleated to form stratum corneum. The role of FLG is to prepare the cells to undergo terminal differentiation (Kuechle et al 2000). In earlier studies FLG has been studied extensively for its loss-of-function related diseases characterised by malformation of the barrier layer (Bussmann et al 2011).…”
Section: Filaggrin -An Important Epidermal Proteinmentioning
confidence: 99%
See 1 more Smart Citation